ANALISIS TARIKKAN PERGERAKAN PENUMPANG ANGKUTAN PENYEBERANGAN PELABUHAN ULEE LHEUE KE ZONA PERDAGANGAN DAN JASA DAN ZONA PERKANTORAN DAN PENDIDIKAN - Wan Achmad R. Runatha; Renni Anggraini; Sugiarto Sugiarto (Prodi Magister Teknik Sipil Unsyiah, 2019)
The city of Sabang is one of the most iconic tourism spots in Aceh Province. The Ulee Lheue Port is one of the most important accesses to Sabang, which is located in Banda Aceh City, the capital of Aceh Province. So that crossing activities carried out by both local residents and tourists will always pass through Banda Aceh. Along with the developments in each of these regions, the travel demand in a form of increased movement activity has been rising. The purpose of this study is to get a trip attraction model of Ulee Lheue Port ferry boat passenger that attracted to two destination zones in Banda Aceh by using multiple linear regression analysis methods and calculated by using SPSS software based on socio-economic and travel behavior data as independent variables (X) and the movement frequency as dependent variable (Y). Based on the analysis results, the model with each trip destination zone has a different travel behavior. The most influential variables for trip attraction model of the Ulee Lheue Port ferry passengers trip to trade and service zone are work activity (X12D), gender (X1), and income (X3). The most influential variables for the trip production model of the Ulee Lheue Port ferry passengers trip to office and educational zone are government workers (a type of work) (X6C), age (X2), gender (X1), crossing time (X11), private employees (a type of work) (X6D).